Pembulatan Uang Sisa - Lina Khalida; Muhammad Arsad Nasution (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The fundamental problem in this research is the element of compulsion for unilateral actions in rounding off the remaining money. In this problem, the researcher wants to know the form of refunding the remaining money with a small nominal in buying and selling transactions at the Ita Siregar Store and the Fiqh Muamalah review of the practice of rounding.This research uses field research, namely data collection is carried out by direct observation to Ita Stores and interviews with sellers and buyers who know the practice of rounding up the remaining money in buying and selling transactions. After that, it is analyzed, namely explaining the views on buying and selling and rounding off the remaining money from Fiqh Muamalah.In the implementation of the pillars and terms of buying and selling with the practice of rounding up the remaining money at the Ita Siregar Shop, it is in accordance with Muamalah Fiqh. However, rounding off the remaining money in buying and selling based on sharia principles, one of which is to prioritize the principle of willingness when the transaction is not in accordance with Fiqh Muamalah because in practice, there is still an element of coercion.The factor in the rounding up of the remaining money from the Ita Siregar Shop is the rounding of the remaining money due to the absence of change with a small nominal value, making transactions easier and as a means of giving alms. So the thing that must be done is to make a nominal calculation of the price of goods at the right price or the nominal that is still circulating a lot to avoid small fractional nominals.